Poblaciones de fijadores biológicos de nitrógeno en la producción del cultivo de soya en la zona de Los Ríos - Palma Ramírez, Ítalo Andrés (2022)
The present essay makes a reference on the populations of biological nitrogen fixers in the production of the soybean crop in the Los Ríos area. Biological nitrogen fixation takes place in the root nodules. The nodules are the result of a perfect symbiotic relationship between the plant and the bacteria. The bacteria that are part of these root nodules are called rhizobia. The conclusions determine that to improve the availability of nitrogen, nitrogen-fixing microorganisms are used, within which two groups are distinguished: "symbiotic" microorganisms that fix nitrogen in association with plants, these microorganisms called rhizobia colonize and form nodules in the plant roots where gaseous nitrogen is reduced to ammonium; and the "asymbiotic" (or free-living) type microorganisms that provide the environment with nitrogenous compounds such as ammonium, used by plants and the symbiotic association of Nitrogen in soybean cultivation allow maintaining the sustainability of agricultural systems, benefiting, not only to crop yields, but also to the physical and chemical conditions of the cultivated soils.